Filmes automontados de nanopartículas de magnetita e polipirrol na determinação analítica de metilparabeno - Lima, Lucas de (Universidade Federal de São Carlos, 2020)
Parabens are esters derived from para-hydroxybenzoic acid used as antimicrobials and bactericides in cosmetics, personal hygiene and cleaning products, food and medicines. Side effects have been observed due to the bioaccumulation of these compounds in the mammary region. Methylparaben (MeP), the most common form, can cause cancer in womb and ovary, endometriosis and other hormonal problems in women. Breast milk is, in most cases, the only source of newborn feeding and it has an average of 22.0 μg L-1 of MeP. This value is considered risky, since the acceptable amount of parabens for children is 10.2 ng kg-1. Considering this, the present work aims the detection of MeP in samples of urine and breast milk statistically comparing the electroanalytical method of Differential Pulse Voltammetry (DPV) with the official method of Capillary Electrophoresis (CE), using modified electrodes. The magnetite nanoparticles presence with polypyrrole (Fe3O4-np/Ppy)3 on the gold substrate surface (Au), allowed the increased charge transfer rate of the target molecule. The size of the Fe3O4-np was determined by SEM and SPR with an average diameter of 16.28 ± 2.48 nm and 14.8 nm, respectively. Besides, a linear growth and good interaction between Fe3O4-np and Ppy in film LbL were observed, as can be seen in UV-vis spectra by the bands at 224, 360 e 480 nm and FTIR spectra by the bands at 561, 632, 1576, 1419, 1041 e 936 cm-1. The DPV method detected MeP in urine and breast milk in a range of 16.43×10-6 – 131.40×10-6 mol L-1 and limits of detection were 3.76×10-8 mol L-1 and 7.11×10-8 mol L-1, respectively. Both methods were compared by statistical method Miller-Miller. The good linearity obtained in the statistical method indicating that the electrochemical sensor and the analytical method presented very close results, showing good accuracy between both methods, which allows discussion concerning the use of electroanalytical methods as alternative forms of official analysis methods in biological fluids containing MeP.
Self-assembled films of magnetite and polypyrrole nanoparticles in the analytical determination of methylparaben
Keywords: filmes LbL, Metilparabeno, tratamento estatístico, DPV, CE, Nanopartículas de magnetita, polipirrol.; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS